Assessing quality in midwest adult degree completion programs: an exploratory study - McRay, Jeni (Kansas State University, 2005)
There has been a steady rise in the number of adult degree completion programs in the last twenty years, and predictions indicate the trend will continue. Simultaneously there is a growing concern for quality in higher education. One of the ways that any organization can assess quality is to gain consensus from a variety of stakeholders as to what institutional goals should be pursued and then measure the level to which those goals are met. The Institutional Goals Inventory consists of 90 goal statements that measure 20 outcome and process goal areas and asks a variety of stakeholders to assess perceptions of both real and ideal goals within an institution. This exploratory, descriptive study polled faculty, students and administrators (n=224) in three Kansas area adult degree completion programs. Questions guiding this study included finding out what goal areas the various stakeholders deemed most and least important, whether or not there was a significant difference in those perceptions between stakeholder groups and/or institutions, and how well each of the institutions is meeting the goals their stakeholders deem most important. Results indicate that all stakeholder groups agree that the Principles of Good Practice for Alternative and External Degree Programs both is and should be important in these programs. Other highly ranked real and ideal goal areas were Academic Development, Community, and Intellectual Orientation. The results also show that while there is a fair amount of consensus among and between stakeholders and institutions on real and ideal goal in these programs, in virtually all instances the stakeholders rated all ideal goal areas as significantly higher than the real goal areas. Several recommendations for adult degree completion programs are offered as well as a lengthy list of suggestions for future research.
Keywords: Adult degree completion programs; Higher education administration; Institutional goals; Adult education; Adult and Continuing Education (0516); Higher Education (0745)